2017
DOI: 10.1002/arch.21432
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two groups of Spodoptera exigua Hübner (Lepidoptera: Noctuidae) C‐type lectins and insights into their role in defense against the densovirus JcDV

Abstract: Insect innate immunity relies on numerous soluble and membranebound receptors, named pattern recognition proteins (PRPs), which enable the insect to recognize pathogen-associated molecular patterns. C-type lectins are among the best-studied PRPs and constitute the most diverse family of animal lectins. Here we have charac- The results showed that Se-BLL3 specifically reduce the mortality of Spodoptera frugiperda larvae caused by JcDV. In contrast, no such effect was observed with S. exigua larvae. In a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The details of these CTLs spatial structures are shown in Supplementary Table 3 . It has been reported that CTLs are widespread in lepidopteran insects and some CTLs from bracoviruses horizontally transferred into genomes of nonparasitized hosts ( 50 , 52 ), we performed the PCR experiment with specific primers of CvBV_28-1 using the DNA as template from parasitized and nonparasitized P. xylostella larvae. The results showed that CvBV_28-1 derived from C. vestalis bracovirus could be detected in the parasitized hosts, but this gene did not exist in nonparasitized host larvae ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of these CTLs spatial structures are shown in Supplementary Table 3 . It has been reported that CTLs are widespread in lepidopteran insects and some CTLs from bracoviruses horizontally transferred into genomes of nonparasitized hosts ( 50 , 52 ), we performed the PCR experiment with specific primers of CvBV_28-1 using the DNA as template from parasitized and nonparasitized P. xylostella larvae. The results showed that CvBV_28-1 derived from C. vestalis bracovirus could be detected in the parasitized hosts, but this gene did not exist in nonparasitized host larvae ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to two classic properties of CTLs mentioned above, insect CTLs are able to mediate other innate immune responses, including opsonization, nodule formation, phagocytosis, encapsulation/melanization and prophenoloxidase activation ( 48 , 49 ). Recently, it has been reported that some insect CTLs originated from PDVs through horizontal gene transfer, and the domestication of these CTLs presents new adaptations and confers the host with protection against baculoviruses ( 50 52 ). Given the special biological features of PDVs, CTLs from PDVs in parasitized hosts might be necessary for wasp offspring survival.…”
Section: Introductionmentioning
confidence: 99%
“…Most insect CTLs are established as strongly inducible secretory proteins produced in response to in vivo stimulations or challenges with pathogens [ 15 , 19 , 20 ]. CTLs act as PRRs in the extracellular environment; they recognize and bind to PAMPs via characteristic motifs localized within the CTL carbohydrate-recognition domain (CRD)—referred to as CLECT on SMART (accession number: SM00034)—overall playing an important role in both antiviral and antibacterial defenses [ 19 , 20 ]. In vertebrates, such motifs are conserved as Glu-Pro-Asn (EPN) or Gln-Pro-Asp (QPD) and are specific for mannose/glucose or galactose carbohydrates [ 21 ].…”
Section: Resultsmentioning
confidence: 99%